Pendampingan penerapan teknologi sistem monitoring dan penyiraman berbasis IoT pada budidaya tanaman obat keluarga - Ilham Sayekti; Bambang Supriyo; Sri Kusumastuti; Bangun Krishna; Vinda Setya Kartika; Kusno Utomo; Dadi Dadi; Samuel Beta; Tulus Pramuji; Achmad Fahrul Aji (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
Assistance in the application of IoT-based monitoring and watering system technology in the cultivation of family medicinal plants (Toga) for the PKK group managing the Tosabu garden, Kramas Sub-district, Tembalang District, Semarang, aims to assist park managers, namely the Kramas Village PKK administrator, in caring for and cultivating various types of medicinal plants in a mini greenhouse with an area of 40 m2. Watering plants is a significant problem during the dry season. In addition, the restrictions on activities during the COVID-19 pandemic have also become an obstacle for park managers to take care of plants intensively. This happens because there is no regular system for watering plants due to the busyness of the gardeners. The implementation method in service starts from site surveys and problem inventory, system design and manufacture, installation, training for managers, and evaluation. Technology was designed and built using Arduino Uno and Nodemcu ESP8266 as the central controller and the Blynk application to monitor and control the system using a smartphone. The system is equipped with several sensors, including DHT11 as a temperature and humidity sensor, a soil moisture sensor, and a rain sensor. Twenty-four mini sprinkler sprayer nozzles are used as plant sprinklers installed on each side and top of the greenhouse. The sprinkler and plant monitoring system that has been made has been successfully tested and works well. The plant watering system created can operate automatically using a smartphone and manual operation. The results of the application of this technology can be used by partners and can overcome the problems faced in treating and cultivating family medicinal plants efficiently